Prime Minister's Decree No. 876 of the year 2023 Amending Certain Provisions of Prime Minister’s Decree No. 3099 of the Year 2019 Organizing The Cases of Granting The Egyptian Citizenship to Foreigners = قرار رئيس مجلس الوزراء رقم 876 لسنة 2023 بتعديل بعض أحكام قرار رئيس مجلس الوزراء رقم 3099 لسنة 2019 بتنظيم حالات منح الجنسية المصرية للأجانب - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic